Work Schedules and Community Ties. (May 2014) - Cornwell, Benjamin; Warburton, Elizabeth
Little is known about how work schedules affect social connectedness beyond family relationships. The authors use detailed time diary data from 12, 140 respondents in the 2008 through 2010 American Time Use Surveys to examine how work schedules affect six forms of community involvement. Results show that night and evening shift work reduces community involvement, but only on weekdays. Daytime shifts reduce community involvement when they are very short, when they involve working from 8 to 5 instead of from 7 to 4, and when they are on weekends. These results call into question tacit assumptions about how shift work affects workers' social lives.